Inclusive Education and avenues of learning for learners with Muscular Dystrophy: A Case Study - Kirti Rastogi, Shruti; Nidhi, Geetika (International Journal of Psychosocial Rehabilitation, 2025)
Muscular dystrophy is a group of diseases that cause progressive weakness and loss of muscle mass. In muscular dystrophy, abnormal genes (mutations) interfere with the production of proteins needed to form healthy muscle. Consequently, with time, the afflicted lose the ability to even carry out an elemental function like body movements. It is an agonizingly painful phase in the patients’ lives as they battle with the disease that threatens to choke their chances of sustenance with each passing day. Even more dismal is the lack of awareness regarding the disease; hence, the possibilities of creating appropriate scaffolds to facilitate the well-being of people afflicted with muscular dystrophy are minimal at present. This lacuna is more entrenched in education. It is pertinent to refer to the Rights of Persons with Disabilities Bill—2016 in this context. With the amendment now, the Government of India has extended the ambit of disabilities from 7 to 21, with muscular dystrophy indicated as a separate class of specified disability. Given this premise, it is imperative to note that it is now a mandatory clause for all the government-funded educational institutions as well as those recognized by the government to proffer inclusive education to such learners. In this contextual frame, this study attempts to present 5 case studies pertaining to learners with muscular dystrophy. The author has personally witnessed a lack of information among the parents and, therefore, their inability to help their children affected with muscular dystrophy, especially in the case of Duchenne muscular dystrophy. Hence, as a long-time personal goal, she developed this study to address this lacuna. Case studies are based on semi‐structured interviews that were conducted with five parents. Analysis of the interview data indicated the willingness of these parents to share information to empower others like themselves. The study reaches conclusions that recommend a host of solutions aimed at redefining pedagogies to empower the learning abilities of students with muscular dystrophy.